Computational Assessment of a Modular Composite Wind Turbine Blade Joint - Nanami, Norimichi; Ochoa, Ozden O. (Journal of Technology Innovations in Renewable Energy, 2016)
Wind energy is one of the most promising and mature alternatives to satisfy the global demand for energy as the world population and the economic activity surge. The wind energy market has grown rapidly in the last couple of decades, boosting up the size of wind turbines to generate higher power output. Typically, the larger/longer blade designs rely on hybrid material systems such as carbon and/or glass fiber (CF/GF) reinforced polymers to improve specific stiffness/strength and damage tolerance. Herein, we propose a computational design concept for a modular hybrid composite wind turbine blade that maintains its structural integrity and serviceability requirements. The modular configuration will simplify manufacturing-assembly processes and reduce expenses both in transportation and facilities requirements. The 80 m blade in this study is composed of two sections that are joined together with an innovative compression joint. Our results when compared to a single continuous blade, showed no significant alterations to its structural response. It is concluded that the proposed computational design concept that allow two modular blades to create full-length blade with robust joints is achievable. This modular concept can be easily extended for further multi-section modular blade configurations.